High Gain CMOS Transimpedance Amplifier For Near Infrared Spectroscopy Applications. Issue 1 (1st September 2022) - Muthukumaran, B.; Ramachandran, B.
Abstract: In this paper, design and analysis of High Gain CMOS Transimpedance Amplifier (HGCTIA) is presented which is greatly necessitated for frequency domain functional Near Infrared Spectroscopy (FD-f NIRS). Generally, feedback resistor and drain resistor play a major role in deciding TIA gain and bandwidth. Most of the research work have utilized only feedback resistor and drain resistor. Here, the gain improvement is greatly achieved by replacing the drain resistor by an active inductor which is designed using CMOS transistor. The active inductor loaded based TIA exhibits only 0.01mW power dissipation which is comparatively lesser than previous research works. Also the proposed design achieves maximum value of transimpedance gain 140dB, bandwidth of 10 MHz, where average noise over the bandwidth is 4.6pA/√Hz with 0.68nArms . Input referred noise is 3.38pA/√Hz. These results are obtained by simulating the proposed approach using cadence 45nm technology. The simulated results shows that the proposed HGCTIA is superior in terms of power, gain and bandwidth.